Anti-Neuroinflammatory ent-Kaurane Diterpenoids from Pteris multifida Roots - Kim, Jung Wha (Molecules, 2016)
Activated microglia are known to be a major source of cellular neuroinflammation which causes various neurodegenerative diseases, including Alzheimer’s disease. In our continuing efforts to search for new bioactive phytochemicals against neuroinflammatory diseases, the 80% methanolic extract of Pteris multifida (Pteridaceae) roots was found to exhibit significant NO inhibitory activity in lipopolysaccharide (LPS)-activated BV-2 microglia cells. Three new ent-kaurane diterpenoids, pterokaurane M(1) 2-O-β-d-glucopyranoside (4), 2β,16α-dihydroxy-ent-kaurane 2,16-di-O-β-d-glucopyranoside (10), and 2β,16α,17-trihydroxy-ent-kaurane 2-O-β-d-glucopyranoside (12), were isolated along with nine other known compounds from P. multifida roots. The chemical structures of the new compounds were determined by 1D- and 2D-NMR, HR-ESI-MS, and CD spectroscopic data analysis. Among the isolates, compounds 1 and 7 significantly inhibited NO production in LPS-stimulated BV-2 cells reducing the expression of the cyclooxygenase-2 (COX-2) protein and the level of pro-inflammatory mediators such as prostaglandin E(2) (PGE(2)), tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6. These results suggest that ent-kaurane diterpenes from P. multifida could be potential lead compounds that act as anti-neuroinflammatory agents.